From Production to Preservation: Hand-Painted Magic Lantern Slides from the National Museum of Natural History and Science - Rodrigues, Beatriz Maria Barata (2020)
The present work arises as part of the first systematic investigation on hand-painted magic lantern glass slides resorting to multi-analytical techniques combined with critical analysis of historical written sources on the painting materials and techniques used to produce them. The magic lantern was an optical instrument, used to project images from the seventeenth to the twentieth centuries, that attained great success with high impact on entertainment, science, religion and advertisement. In the framework of this work, five hand-painted magic lantern glass slides from the National Museum of Natural History and Science (University of Lisbon) were studied. The glass support, the colourants and organic media were characterised. The glass was analysed by Micro-Energy Dispersive X-Ray Fluorescence, and the oxide quantification unveiled that the glass belongs to the soda-lime silicate type and was possibly produced between 1870 and 1930 in England. Additionally, considering the standardized size of the slides and the similarity of the subjects represented with other English slides from the nineteenth century, it was possible to narrow the production period of this collection between 1870 and 1900. Ultraviolet-Visible, Micro-Raman and Micro-Fourier Transform Infrared spectroscopies allowed the characterisation of the colourants. The colour palette is composed of Prussian blue, an anthraquinone red lake pigment of animal origin (such as cochineal carmine), an organic yellow whose identification was not yet possible and a carbon-based black pigment. The remaining colours – green, purple and brown – were achieved by mixing the pure pigments. Through infrared analysis, a terpenoid resin such as shellac was identified. The detection of metal carboxylates was essential to assess the state of conservation of the paints. The identification of the main risks that might endanger the collection in study was made, as well as a risk assessment scale. Preventive conservation guidelines were proposed taking into consideration the literature on the preservation of the different materials that compose the magic lantern slides, as well as the results of surveys submitted to national and international museums that hold similar collections.